IMPLEMENTASI UNDANG-UNDANG ASN DALAM TAHAPAN PILKADA KABUPATEN TUBAN TAHUN 2020 - Sutrisno Puji Utomo Sutrisno (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2021)
The purpose of this paper is to: Explain the legal study of the implementation of Law Number 5 of 2014 concerning the State Civil Apparatus (ASN) in the stage of selecting the regional head of Tuban Regency. This research is a type of qualitative research. This research emphasizes on election management institutions, so the main approach used is the institutional network approach to Bawaslu, namely through a legal approach and a conceptual approach. Meanwhile, the legal material uses laws related to elections and its derivatives, namely the Bawaslu regulations in dealing with election violations. The realization of the neutrality of the State Civil Apparatus in the Pilkada can be carried out by optimally involving several related institutions, including the State Civil Apparatus Commission (KASN), Bureaucratic Leaders, Regional Inspectorates, and the Regional Civil Service Agency, the General Election Commission (KPU) and the General Elections Supervisory Agency (KPU). BAWASLU). The results of this study can be explained in the context of the Tuban Regency Pilkada on the legal settlement of findings of violations at the pilkada stage by ASN, the Tuban Regency Bawaslu then sends the results of the study and findings to the State Civil Apparatus Commission and by the institution a warning letter of recommendation is issued to the candidate.